Energy and mechanical aspects on the thermal activation of diaphragm walls for heating and cooling. (March 2020) - Barla, Marco; Di Donna, Alice; Santi, Alessandro
Abstract: Underground geotechnical structures, such as deep and shallow foundations, diaphragm walls, tunnel linings and anchors are being increasingly employed as energy geostructures to exchange heat with the ground by installing absorber pipes into the structural elements. This paper focuses on the application of this technology to reinforced concrete diaphragm walls used for construction of underground car parks, basements and metro stations, with the purpose of heating and cooling the adjacent buildings. Preliminary numerical modelling allowed optimising the geothermal plant design of the diaphragm wall. Then its energy efficiency is investigated through finite element thermo-hydro coupled analyses together with the effects of the thermal activation on the surrounding soil. Finally, finite difference thermo-mechanical analyses are used to study the mechanical effects induced by the thermal activation. Highlights: Thermal and mechanical aspects of energy walls are discussed. The horizontal configuration of pipes geometry allows maximising the heat exchange. Heat exchange between 20 and 25 W/m 2 with static ground water. Heat exchange between 40 and 50 W/m 2 with favourable groundwater flow. Bending moment increase up to 16% due to thermal activation.